Farmed Mussels in the Northeastern U.S. Exclusive Economic Zone: An Opportunity Too Good to Ignore. Issue 4 (30th April 2020) - Mizuta, Darien D.; Wikfors, Gary H.
Abstract : The United States is the top seafood importer in the world. Nevertheless, opportunities to expand national seafood production, such as offshore aquaculture, are restricted by unclear frameworks for licensing, permitting, and regulating new enterprises. Currently, domestic mussel demand is reliant upon international trade but demand could be met by aquaculture within the Exclusive Economic Zone, especially in suitable areas off the Northeast coast. With national public seafood preferences pointing towards the need for a larger mussel farming industry, science‐based efforts to develop offshore farming will contribute to local economies and domestic supply of high‐quality, traceable seafood. Beyond a scientific foundation, perceptions that offshore farming represents environmental and privatization threats instead of a national economic development and sustainable opportunity, will have to be addressed. The situation will only change when managers decide to include offshore aquaculture as one of the many legitimate activities for New England's ocean waters, so that spatial planning can be done and conservation measures and offshore farming develop in tandem.